Do Exchange Rates Affect the Stock Performance of Australian Banks? - Chi, Jing; Tripe, David; Young, Martin (Universiti Utara Malaysia Press, 2010)
It is expected that banks with significant foreign business should be impacted by relative changes in the currency values of the foreign countries where they do business. Using data from January 1997 to March 2007, this study explored this relationship for the four major Australian banks.Contrary to expectations, no significant relationships between Australian bank stock returns and foreign exchange rates were found, raising questions as to the efficiency of stock markets in recognising banks’ foreign exchange exposures arising from their offshore assets and business.